Agroecological cultivation of cherry tomatoes using biofertilizers under protected environment (Bioagro, 2025)
Cherry tomato has been increasing its market demand in Brazil, primarily due to desirable consumption characteristics. Studies aimed at optimizing the agroecological cultivation of cherry tomato remain limited and inconclusive. The aim of this work was to evaluate the effect of biofertilizers on the plant development and production of cherry tomatoes in the cerrado of Roraima. The experiment was carried out in a greenhouse at the Agricultural Sciences Center of the Federal University of Roraima, Boa Vista. For the experiment, a randomized block design was used, arranged in a 2 x 4 factorial scheme (2 types of biofertilizers and 4 doses), with four replications. Two types of organic fertilizer were evaluated, using ordinary biofertilizer (BC: 50 % cattle manure + 50 % water) and enriched biofertilizer (BE: 15 % cattle manure + 15 % poultry manure + 10 % carbonized rice husk + 10 % gravel powder + 50 % water), with the following doses (0; 800; 1600 and 2400 mL·plant-1). The analysis revealed a significant effect of the dose of biofertilizer, type of biofertilizer and their interaction, promoting increasing responses in the dry mass of the aerial part, dry mass of the roots, number of fruits produced and the equatorial diameter of the fruits. However, the plants treated with enriched biofertilizer showed higher values when compared to the plants treated with ordinary biofertilizer. Increasing doses of biofertilizers promoted higher yields, regardless of treatment. The use of biofertilizers in increasing doses promotes the vegetative and productive development of cherry tomatoes.
Keywords: Growth; interaction; organic production; Solanum lycopersicon